CAN HUMAN RESOURCES INDUCE SUSTAINABILITY IN BUSINESS? MODELING, TESTING AND CORRELATING HR INDEX AND COMPANYS BUSINESS RESULTS - Zubović, Jovan; Jeločnik, Marko; Subić, Jonel (Economics of Agriculture, 2015)
In this paper the authors analyze the impact of the composite human resource index on sustainable growth in a specifc business sector in a transition country. Sustainability of countrys economy is growingly relying on the knowledge economy which has been implemented in strategies of sustainable development throughout Europe. The knowledge economy is mostly based on human resources and the way they are organized and managed in the companies actively operating in competitive markets. In order to confrm importance of the human resources (HR) index, results were tested by means of modeling, measuring and correlating the HR index with business results at micro level. The tests were conducted on the data from the survey in Serbian meat processing industry. The results were then compared with the results from the survey conducted in a fnancial industry. Moreover, a model was made that could be applicable in all countries that do not have available offcial statistic data on the level of investments in human resources. The focus was on determining the correlation direction, and hence creating a research model applicable in all business sectors. It has been found that a signifcant one-way correlation exists between business performance and increased HR index. In that way it has been confrmed that in Serbian economy that has recorded global decrease during transition, certain business sectors, and especially companies with high levels of investments in improving its HR index record above average and sustainable growth.